Spatial patterning of pigmentation in evergreen leaves in response to freezing stress - NICOTRA, A. B.; HOFMANN, M.; SIEBKE, K.; BALL, M. C. (Plant, cell and environment, 2003)
ABSTRACT Evergreen leaves of temperate climate plants are often subject to frosts. Changes in carbon gain patterns arise from freezing‐related tissue damage, and from interactions between light and temperature stress. We examined relationships between spatial patterns in freezing and concentrations of chlorophyll. Spatial patterns in pigmentation in leaves that had or had not been exposed to naturally occurring frosts were determined by conventional extraction techniques combined with high‐resolution hyperspectral imaging of reflectance from intact leaves. Predictive indices were developed to relate reflectance to chlorophyll content and chlorophyll a/b ratios within intact leaves. Leaves exposed to frosts had lower chlorophyll contents and more variable a/b ratios than protected leaves. In frost‐affected leaves, chlorophyll content was highest near leaf centres and decreased toward leaf tips and margins. Decline in chlorophyll content was associated with shifts in chlorophyll a/b ratios and increases in red pigmentation due to anthocyanin, with effects being greater on leaf sides exposed directly to the sun. These altered pigmentation patterns were consistent with patterns in freezing. The present results illustrate the fine scale of spatial variation in leaf response to freezing, and raise important questions about impacts of freezing on photosynthetic function in over‐wintering evergreens.